Improving the Performance of Bamboo and Eucalyptus Wood fiber/Polypropylene Composites Using Pectinase Pre-treatments. (2nd January 2018) - Li, Xiaoping; Xiao, Rui; Morrell, Jeffrey J.; Wu, Zhangkang; Du, Guanben; Wang, Shugang; Zou, Chenggang; Cappellazzi, Jed
Abstract : The potential for using pectinase as a pre-treatment to improve the properties of bamboo or eucalyptus fibers for use in a woody fiber/polypropylene (PP) composite was compared with the addition of a silane coupling agent or NaOH pre-treatment. Pectinase pre-treatment reduced the amount of pectin in both fibers (p < 0.0001) and this reduction was associated with improved tensile strength, modulus of rupture and modulus of elasticity (p < 0.001) of bamboo, or eucalyptus fiber-based composites. Pre-treatment had no consistent effects on the thickness swell or water absorption. The addition of a coupling agent produced similar improvements in panel properties (p < 0.05), but also markedly reduced moisture absorption and thickness swell (p < 0.05). Sodium hydroxide pre-treatment had no consistent effects on panel properties, although it did appear to affect thickness swell. Short pectinase pre-treatment might be useful for enhancing the properties of woody tissue/PP composites while reducing but not completely eliminating the need for coupling agents.